Public ritual, martial forms and the Restoration of the monarchy in English towns - Calladine, Amy (Wiley, 2018)
This article explores the public ceremonies chosen to mark the restoration of Charles II in a range of provincial towns. It emphasizes both the extent of performative creativity and the prominence of martial forms at the proclamation in May 1660 and the coronation in April 1661. Using evidence from contemporary printed sources and the records of civic government, it demonstrates how local authorities could use public ritual to negotiate instabilities linked to the ‘Old Army’ of the commonwealth and the practical logistics of the new settlement while continuing to formulate more specific statements on the honour and security of the immediate vicinity.